Misconception identification in the buffer solutions: how to prepare the first-year student to learn general chemistry - Asih Widi Wisudawati; Fidia Lukita; Sarima Saharani; Alviana Mahbubah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Understanding Buffer solutions is required for university students who will take a general chemistry course. Conceptually, buffer solutions are needed to prepare chemical experiments. Due to the nature of the buffer concept, students often hold misconceptions. This study aims to analyze the misconceptions of Chemistry Education students on buffer solutions using a two-tier diagnostic test instrument. This study used a descriptive method with 43 Chemistry Education first-year students enrolled in 2025 at UIN Sunan Kalijaga Yogyakarta as participants. Data collection was conducted through Google Forms using a two-tier diagnostic test consisting of 10 multiple-choice questions with explanations. The results showed that misconceptions were still significantly found, especially in the basic concepts of buffer solution properties against pH changes, the formation of buffer solution systems, the role of stoichiometry in buffer reactions, and the effect of buffer component concentration on buffer capacity. The highest percentage of misconceptions was found in the sub-concepts of buffer solution formation and loss of buffer properties. These findings indicate that some students still understand buffer solutions procedurally and absolutely, without understanding the underlying acid-base equilibrium mechanism. Therefore, learning strategies that emphasize conceptual understanding, the use of multiple representations, and the use of diagnostic tests to identify and reduce misconceptions early on are needed.